Religious Animals and Animal Gods: Review of Barbara Allen, Animals in Religion: Devotion, Symbol & Ritual, and Donovan O. Schaefer, Religious Affects: Animality, Evolution, and Power - Marovich, Beatrice (Humanimalia, 2018)
Barbara Allen. Animals in Religion: Devotion, Symbol, and Ritual. Reaktion Books, 2016. 560 pp. £40.00 (hb). Donovan O. Schaefer. Religious Affects: Animality, Evolution, and Power. Duke University Press, 2015. 304 pp. 94.95 (hb), 24.95 (pb).